Analisis Jaringan (Social Network Analysis) terhadap Struktur Operasi Kejahatan Siber Terorganisir di ASEAN - Astrid Laila (Universitas Sains dan Teknologi Komputer, 2025)
This study investigates the structural dynamics of organized Cybercrime networks operating across ASEAN by employing Social Network Analysis (SNA) to uncover relational patterns, key actors, and functional subgroups within digital criminal ecosystems. Drawing on validated secondary data and network modeling, the analysis demonstrates that Cybercriminal operations in the region exhibit scale-free characteristics, with a small number of highly influential nodes serving as central coordinators and connectors across multiple communities. These structural properties reveal that Cybercrime in ASEAN is sustained not only by technical capabilities but also by interconnected social relationships that enable resource sharing, role specialization, and cross-border collaboration. The findings provide empirical insight into the architecture of Cybercriminal networks, offering theoretical contributions to digital criminology and practical implications for regional law enforcement, particularly for designing targeted interventions to disrupt high-impact nodes. The study also highlights several limitations related to data availability and recommends deeper integration between SNA, digital forensics, and intergovernmental data-sharing mechanisms in future research.